Cation‐Alloying‐Induced Blue‐Shifted and Wide‐Spectrum Polarization‐Sensitive Photodetection in Quasi‐1D SbBiS3. Issue 7 (5th June 2022) - Yang, Wen; Xiong, Tao; Liu, Yue-Yang; Yang, Juehan; Xu, Qun; Wei, Zhongming
Abstract : Quasi‐1D ternary semiconductors have attracted considerable attention recently because of their additional bandgap engineering deriving from the variable stoichiometry. Herein, SbBiS3 single crystals are successfully synthesized by chemical vapor transport (CVT) method. The basic characterizations combined with theoretical calculations reveal that SbBiS3 semiconductor has an intrinsically low symmetry structure and in‐plane anisotropy of optical absorption. Significantly, the bandgap of SbBiS3 shows a blue‐shifted compared to the bandgaps of binary Sb2 S3 and Bi2 S3 . Moreover, the quasi‐1D SbBiS3 ‐based photodetector shows a wide‐spectrum photosensitivity (360–1064 nm), a fast response speed ( τ rise ≈ 10 μs and τ decay ≈ 94 μs) at 532 nm, a high photoresponsivity (6.82 A W −1 ) at 360 nm. In addition, the photodetector exhibits an anisotropic photocurrent ratio up to 1.12 at 808 nm. The work demonstrates the SbBiS3 prepared by cationic alloy is a promising candidate for the application of polarized optoelectronics. Abstract : The theoretical calculation results and experiment results confirm that the bandgap widening and the optical absorption blue shift of SbBiS3 are caused by cationic alloying. These results will ignite research efforts to the discovery and fabrication of V–VI semiconductors, which will become promising candidates for future polarization‐sensitive photodetectors.